2021
DOI: 10.3390/foods10071604
|View full text |Cite
|
Sign up to set email alerts
|

Government Policy for the Procurement of Food from Local Family Farming in Brazilian Public Institutions

Abstract: This study aims to explore and compare Brazilian public institutional food services’ characteristics concerning the implementation of the government policy for the procurement of food from family farming (FF) and the opinions of food service managers on the benefits and difficulties of its implementation. We conducted a cross-sectional study employing an online questionnaire. The results were stratified by purchase. The Chi-square and Fisher’s Exact tests were applied. Five hundred forty-one food services’ man… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
16
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 8 publications
(18 citation statements)
references
References 28 publications
2
16
0
Order By: Relevance
“…The positive influence brought in school feeding by family farming is evident regarding the increase in variety and supply of horticulture, in natura, or minimally processed products when compared with ultra-processed ones [19,[48][49][50][51]. However, at the same time, this characteristic proves positive in promoting the health of students, as well as leading to positive changes in their consumption pattern [52], the quality of those foods and the way they are produced, as well as the lack of variety produced (especially for foods of local sociobiodiversity) and sold by those producers also carries other important discussions.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The positive influence brought in school feeding by family farming is evident regarding the increase in variety and supply of horticulture, in natura, or minimally processed products when compared with ultra-processed ones [19,[48][49][50][51]. However, at the same time, this characteristic proves positive in promoting the health of students, as well as leading to positive changes in their consumption pattern [52], the quality of those foods and the way they are produced, as well as the lack of variety produced (especially for foods of local sociobiodiversity) and sold by those producers also carries other important discussions.…”
Section: Discussionmentioning
confidence: 99%
“…Studies have shown that meats and processed meat products purchased by public education institutions are rarely local in origin [61,62]. However, this group of foods still features within the scope of supply of family farming in the public calls, also with special attention to processed foods [49], signaling that there is potential for the distribution and production of different food groups by family farmers.…”
Section: Discussionmentioning
confidence: 99%
“…A study carried out by [47] with municipal public managers investigated the purchase of food from family farming in a broader way than the PNAE and identified that the purchase of products is more frequent among managers who work in municipalities with less than 50,000 inhabitants, or in self-managed (there is neither leadership nor hierarchy) and educational institutions. It also identified that municipalities that purchase products from family farming promote healthier and sustainable food actions.…”
Section: The National School Feeding Program (Pnae)mentioning
confidence: 99%
“…Adequate and healthy diets imply choosing and consuming balanced and adequate foods on nutrients and amount, variety, and sustainable aspects. Therefore, achieving the main social, economic, environmental, cultural, and security goals [ 1 , 3 , 6 , 7 , 8 , 9 , 10 , 11 , 12 , 13 , 14 , 15 , 16 ]. Food production must also be alert to the waste produced in the food chain related to environmental pollution and food waste that could be used to feed food-insecure people [ 10 , 15 , 17 ].…”
mentioning
confidence: 99%
“…In order to support sustainable and healthy diets and food security, it is also essential to search for alternatives to stimulate local production and regional food consumption. Other priorities are reducing animal suffering and meat consumption, food production in sufficient quantity and quality with the least possible waste production, and understanding the main aspects of food, nutrition, society, and the environment [ 11 , 12 , 13 , 14 , 15 , 16 , 17 , 18 , 19 , 20 , 21 , 22 ].…”
mentioning
confidence: 99%